Essential features of the innovative environment in general educational institutions (Pedagogy of Higher and Secondary Education, 2013)
Konovalchuk I. I. Essential features of the innovative environment in general educational institutions.The article reviews the essential features of the structure, function and criteria for innovative environment of an educational institution. From the standpoint of systematic approach innovative environment is defined as the integrity of socio-psychological, organizational, educational, informative and communicational, substantial, technological and other conditions that, as a unity, form the means of stimulation, support, management, reflection for the innovative activity of educators and their professional development. As such the innovative environment is a combination of innovations that create new opportunities for the development of educational institution.
Keywords: innovation; environment; environmental approach; innovative environment of the institution